MOG Antibody-Associated Disorders Following SARS-CoV-2 Vaccination: A Case Report and Literature Review - Matsumoto, Yuki; Ohyama, Ayane; Kubota, Takafumi; Ikeda, Kensuke; Kaneko, Kimihiko; Takai, Yoshiki; Warita, Hitoshi; Takahashi, Toshiyuki; Misu, Tatsuro; Aoki, Masashi (Frontiers in Neurology, 2022)
Myelin oligodendrocyte glycoprotein (MOG) antibody-associated disorder (MOGAD) is a newly identified autoimmune demyelinating disorder that is often associated with acute disseminated encephalomyelitis and usually occurs postinfection or postvaccination. Here we report a case of MOGAD after mRNA severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination. A previously healthy 68-year-old woman presented to our department with gradually worsening numbness on the right side of her face, which began 14 days after her second dose of an mRNA-1273 vaccination. The patient's brain MRI revealed a right cerebellar peduncle lesion with gadolinium enhancement, a typical finding of MOGAD. A neurological examination revealed paresthesia on her right V2 and V3 areas. Other neurological examinations were unremarkable. Laboratory workups were positive for serum MOG-IgG as assessed by live cell-based assays and the presence of oligoclonal bands in the cerebrospinal fluid (CSF). The patient's serum test results for cytoplasmic-antineutrophil cytoplasmic antibodies, perinuclear-cytoplasmic-antineutrophil cytoplasmic antibodies, GQ1b-antibodies, and aquaporin-4 antibodies (AQP4-IgG) were all negative. Tests for soluble interleukin (IL)-2 receptors in the serum, IL-6 in the CSF and skin pricks, and angiotensin converting enzyme tests were all unremarkable. The patient was diagnosed with MOGAD after receiving an mRNA SARS-CoV-2 vaccination. After two courses of intravenous methylprednisolone treatment, the patient's symptoms improved and her cerebellar peduncle lesion shrunk slightly without gadolinium enhancement. To date, there have only been two cases of monophasic MOGAD following SARS-CoV-2 vaccination, including both the ChAdOx1 nCOV-19 and mRNA-1273 vaccines, and the prognosis is generally similar to other typical MOGAD cases. Although the appearance of MOG antibodies is relatively rare in post-COVID-19–vaccine demyelinating diseases, MOGAD should be considered in patients with central nervous system (CNS) demyelinating diseases after receiving a SARS-CoV-2 vaccine.